Bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material and preparation method thereof
By adopting a bionic layered spiral continuous carbon fiber reinforced structure in ceramic matrix composite materials, and using 3D printing and impregnation technology, the problem of difficulty in balancing the strength and toughness of existing ceramic materials is solved, achieving high strength and high toughness, and simplifying preparation process.
Patent Information
- Application Number
- CN202411461244.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
AI Technical Summary
Existing bionic ceramic materials are difficult to improve the strength and toughness of ceramic materials at the same time, and the preparation process is complicated.
The bionic layer -shaped spiral continuous carbon fiber enhances ceramic base composite materials. The ceramic support main body is printed through 3D, and a multi -layer hole is set and continuous carbon fiber enhances thermosettic resin to form a spiral rotation structure.
The high strength and high toughness of ceramic base composite materials are achieved, the preparation process is simplified, and the crack expansion can be resisted under high load.
Smart Images

Figure CN119330732A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of bionic materials, in particular to a bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material and a preparation method thereof. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Structural ceramics, with their high melting point, high hardness, high wear resistance, oxidation resistance, and corrosion resistance, can withstand many harsh operating environments and therefore have important applications in metallurgy, aerospace, energy, machinery, optics, and other fields. However, brittle fracture is a key issue facing the application of structural ceramics. Simultaneously improving the flexural strength and fracture toughness of structural ceramics has been a research focus in this field.
[0004] Biomimetic ceramics incorporate natural biological structures into artificial ceramic systems to enhance their strength and toughness. However, existing biomimetic ceramics offer limited improvements in both strength and toughness, and even struggle to achieve both simultaneously. Furthermore, the raw materials used and the preparation steps involved are complex. Therefore, developing a ceramic material that is both easy to prepare and exhibits both high strength and toughness is an urgent challenge. Summary of the Invention
[0005] In view of this, the present invention provides a bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material and a preparation method thereof. The ceramic matrix composite material provided by the present invention has both high strength and high toughness, and the preparation method is relatively simple.
[0006] In the first aspect, the present invention provides a bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material, including a ceramic support body, wherein a plurality of layers of channels are arranged inside the ceramic support body, and each layer of channels is provided with a plurality of channels parallel to each other; the central axis of the plurality of layers of channels is rotated layer by layer at a set angle along the hierarchical extension direction, and the interior of the channels is filled with continuous carbon fiber reinforced thermosetting resin.
[0007] Preferably, the central axis of the topmost layer of the ceramic support body is parallel to the length direction of the ceramic support body.
[0008] Furthermore, the planes where the channels are located are parallel to each other, the central axis of the multi-layer channels is rotated 45 degrees layer by layer along the direction perpendicular to the plane where the channels are located, and 5 layers of channels are arranged inside the ceramic support body.
[0009] Preferably, each layer of channels is provided with at least three channels parallel to each other; the distances between adjacent channels in each layer of channels remain the same; and the total volume of the channels accounts for more than 40% of the volume of the ceramic support body.
[0010] Preferably, the material of the ceramic support body is selected from one or more of alumina, silicon oxide or zirconium oxide.
[0011] Preferably, the continuous carbon fiber reinforced thermosetting resin comprises carbon fiber bundles and thermosetting resin arranged sequentially from the inside to the outside.
[0012] Furthermore, the carbon fiber bundle is 1-2K carbon fiber; the thermosetting resin is selected from one or more of epoxy resin, bismaleimide resin, thermosetting polyimide resin, phenolic resin, cyanate resin or unsaturated polyester resin.
[0013] Furthermore, the volume fraction of carbon fibers in the continuous carbon fiber reinforced thermosetting resin is 3 to 8%.
[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned biomimetic layered spiral continuous carbon fiber reinforced ceramic matrix composite material, comprising the following steps:
[0015] A ceramic support body green body is prepared by 3D printing, and the ceramic support body is obtained by degreasing and sintering. Continuous carbon fibers are inserted into the multilayer channels of the ceramic support body and infiltrated with a thermosetting resin infiltrant. After curing, a bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material is obtained.
[0016] Preferably, the 3D printing is vat photopolymerization 3D printing.
[0017] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0018] (1) The biomimetic layered spiral continuous carbon fiber reinforced ceramic matrix composite material provided by the present invention is designed based on the Brigand microstructure inside the limbs of the peacock mantis shrimp. The structure is composed of a ceramic support body and a continuous carbon fiber reinforced thermosetting resin. The special spiral rotation structure gives the composite material very high strength and toughness, allowing the composite material to withstand high loads and resist crack propagation.
[0019] (2) The present invention uses 3D printing and infiltration to achieve the preparation of bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite materials. The preparation method is relatively simple and has strong designability. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings, which constitute part of the present invention, are intended to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are intended to explain the present invention and do not constitute undue limitations thereon. It is obvious that one of ordinary skill in the art could derive other drawings based on these drawings without inventive effort.
[0021] Figure 1 Schematic diagram of the structure of the bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material according to Example 1 of the present invention;
[0022] Figure 2 is a scanning electron microscope image of the interface between the carbon fiber and the epoxy resin impregnant of Example 1 of the present invention;
[0023] Figure 3 This is a scanning electron microscope image of the interface between Al2O3 and epoxy resin infiltrant in Example 1 of the present invention;
[0024] In the figure, 1. Al2O3 ceramic support body; 2. Epoxy resin impregnation agent; 3. Carbon fiber bundle. DETAILED DESCRIPTION
[0025] It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs.
[0026] The present invention provides a bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material, comprising a ceramic support body, wherein a plurality of layers of channels are arranged inside the ceramic support body, and each layer of channels is provided with a plurality of mutually parallel channels; the central axis of the plurality of layers of channels is rotated layer by layer at a set angle along the hierarchical extension direction, and the interior of the channels is filled with continuous carbon fiber reinforced thermosetting resin.
[0027] The composite material of the present invention is designed based on the Brigand microstructure inside the limbs of the mantis shrimp. The interface between the thermosetting resin and the ceramic support body is tightly bonded, and at the same time, it can effectively coat the carbon fiber, playing a good bonding role. The carbon fiber has high strength and high toughness, which can enable the composite material to withstand higher loads. The central axis of the multi-layer channel is rotated layer by layer along the hierarchical extension direction to form a spirally arranged carbon fiber layer. When the crack reaches the spirally arranged carbon fiber layer, crack deflection and blockage will occur inside the composite material. Crack deflection and blockage can effectively reduce the energy release rate at the crack tip, increase the energy dissipation during the fracture process, and thus increase the toughness of the composite material. When external loading is applied, the carbon fiber can absorb strain to a certain extent, so that the stress is more evenly distributed inside the composite material, reducing the local stress concentration phenomenon. When cracks occur in the composite material, the carbon fiber can also bear the tensile stress inside the material to a certain extent, thereby effectively increasing the strength, stiffness and toughness of the composite material.
[0028] In the present invention, the shape of the ceramic support body is preferably a cuboid, and the central axis of the topmost channel is parallel to the length direction of the ceramic support body. The present invention does not impose any special restrictions on the distance between the topmost channel and the bottommost channel and the top of the ceramic support body.
[0029] In the present invention, the planes of the pores in each layer are parallel to each other, and the central axis of the multi-layer pores is rotated 45 degrees layer by layer along the direction perpendicular to the planes of the pores in each layer. The ceramic support body is provided with five layers of pores. Experimental verification by the present invention shows that when the layers are rotated 45 degrees, the composite material has optimal strength and toughness.
[0030] In the present invention, each channel layer has at least three parallel channels; the distance between adjacent channels in each channel layer remains constant; and the total volume of the channels accounts for at least 40%, preferably 40-45%, of the volume of the ceramic support body. The present invention does not impose any particular restrictions on specific channel parameters, such as pore diameter and pore cross-sectional shape.
[0031] In the present invention, the material of the ceramic support body is selected from one or more of alumina, silicon oxide or zirconium oxide.
[0032] In the present invention, the continuous carbon fiber reinforced thermosetting resin comprises carbon fiber bundles and thermosetting resin arranged in sequence from the inside to the outside.
[0033] In the present invention, the carbon fiber bundle is 1-2K carbon fiber, preferably 1K; the thermosetting resin is selected from one or more of epoxy resin, bismaleimide resin, thermosetting polyimide resin, phenolic resin, cyanate resin or unsaturated polyester resin, preferably epoxy resin.
[0034] Furthermore, the volume fraction of the carbon fibers in the continuous carbon fiber reinforced thermosetting resin is 3 to 8%, preferably 3 to 5%.
[0035] The present invention provides a method for preparing the bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material, comprising the following steps:
[0036] A ceramic support body green body is prepared by 3D printing, and the ceramic support body is obtained by degreasing and sintering. Continuous carbon fibers are inserted into the multilayer channels of the ceramic support body and infiltrated with a thermosetting resin infiltrant. After curing, a bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material is obtained.
[0037] In the present invention, the 3D printing method is vat photopolymerization 3D printing. The present invention does not impose any particular restrictions on the specific steps of preparing the ceramic support body green body by 3D printing, as well as the degreasing and sintering steps. Those skilled in the art can determine the specific process parameters and preparation process based on the selected ceramic material.
[0038] The thermosetting resin impregnant described herein comprises a thermosetting resin and a curing agent. The present invention imposes no particular limitations on the impregnation process; commonly used impregnation methods in the art may be employed. Preferably, the thermosetting resin impregnant is completely immersed in the ceramic support body, which has continuous carbon fibers inserted into its pores, and then cured under vacuum conditions at 80-100°C for 15-40 minutes. Excess resin is then removed and cleaned, followed by curing under vacuum conditions at 110-140°C for 1-5 hours.
[0039] The technical solution of the present invention is further described below with reference to specific embodiments. The following equipment and models are used in the following examples: a vat-based photopolymerization 3D printer (Model: AME RP150); a UV curing chamber (Model: PCU 80); a vacuum drying oven (Model: DZF-6050); a 1700°C box furnace (BR-17M); a dual-beam FIB scanning electron microscope (Model: FIB-SEMGX4); and a universal testing machine (Model: WDW3200).
[0040] Example 1
[0041] This embodiment provides a biomimetic layered spiral continuous carbon fiber reinforced ceramic matrix composite material, the structural schematic diagram of which is shown in FIG. Figure 1 As shown, its preparation method is as follows:
[0042] (1) Draw a three-dimensional model of a biomimetic layered spiral ceramic scaffold. The model structure and parameters are as follows:
[0043] The Al2O3 ceramic support body 1 is 35mm long, 9mm wide, and 9mm high. It has five layers of channels inside. The channel interface is rectangular, 2mm long, and 1.2mm high. The central axis of the five layers of channels rotates 45° from top to bottom. The top layer has three channels, and the central axis of the channels is parallel to the length direction of the ceramic support body 1. The top channel is 0.5mm away from the top of the ceramic support body 1. The distance between adjacent layers is 0.5mm, and the distance between adjacent channels in each layer is 0.8mm. The total volume of the channels is 40.04% of the volume of the ceramic support body 1.
[0044] (2) Reduced photopolymerization 3D printing:
[0045] Preparation of ceramic slurry: First, epoxy resin E51, 1,6-hexanediol diacrylate (HDDA), and trimethylolpropane triacrylate (TMPTA) were mixed in a mass ratio of 1:1:1, and then 1wt.% of 2-hydroxy-2-methyl-1-phenyl-1-propanone was added. Ultrasonic dispersion was performed using an ultrasonic disperser and an electric stirrer, and the mixture was stirred for 20 minutes to obtain a photosensitive resin premix. Secondly, 500nm Al2O3 powder was sieved using a vibrating screen to filter out agglomerated lumps to facilitate the preparation of the slurry. 500nm and 100nm Al2O3 powders and 1wt.% of magnesium oxide powder were thoroughly mixed. Subsequently, the mixed powder was added to the photosensitive resin premix to a mass fraction of 75%. Finally, the premixed slurry was stirred at a speed of 1500 r / min using an electric stirrer for 1 hour. At the same time, the slurry was ultrasonically dispersed using an ultrasonic disperser. After stirring, the evenly mixed ceramic slurry was placed in a vacuum drying oven and defoamed at a negative pressure of -80 kPa for 10 minutes.
[0046] The model of step (1) was printed using v-photopolymerization 3D printing with the following printing parameters: slice layer thickness of 50 μm, laser power of 110 mW, and scanning pitch of 30 μm. After printing, the support structure was separated from the alumina green body; then, the alumina green body was cleaned with anhydrous ethanol to remove excess epoxy resin on its surface; then, the uncured ceramic slurry in the gaps of the alumina green body was cleaned with an air compressor; then, the cleaned alumina green body was placed in an ultrasonic cleaner for ultrasonic cleaning; then, the alumina green body was placed in a UV curing box for curing for 15 minutes to cure the unformed part; finally, it was placed in a vacuum drying oven and dried at a constant temperature and pressure of 70°C for 3 hours.
[0047] (3) Degreasing and sintering:
[0048] The Al2O3 green body obtained by solidification in step (2) is placed in a crucible and then sent to a box furnace for degreasing. After degreasing, it is returned to the box furnace and sintered at 1600°C for 2 hours to finally obtain a dense Al2O3 ceramic support body 1.
[0049] (4) Penetration into carbon fiber bundle 3 and impregnation:
[0050] Insert the 1K carbon fiber bundle 3 into all the pores of the Al2O3 ceramic support body 1 obtained in step (3), then add the epoxy resin impregnant 2 until the epoxy resin impregnant 2 completely immerses the Al2O3 ceramic support body 1 and the carbon fiber bundle 3, and then cure it in a vacuum oven at 95°C for 25 minutes. After taking it out, use an alcohol wipe to clean the excess resin on the surface. After cleaning, place it in a vacuum drying oven again and keep it at a constant temperature of 125°C for 3 hours to completely cure it. The epoxy resin impregnant 2 used is composed of epoxy resin (E51 / 618), curing agent methyltetrahydrophthalic anhydride (MTHPA) and curing accelerator (DMP-30). The molar ratio of the epoxy value of the epoxy resin to the molar amount of the anhydride of MTHPA is 4:3, and the amount of DMP-30 added is 0.1wt% of the epoxy resin impregnant 2.
[0051] Figure 2 A cross-sectional view of the bond between the carbon fiber bundle 3 and the epoxy resin impregnant 2 shows how the fibers are evenly embedded in the resin, tightly bonded and evenly distributed. The presence of resin adhering to the carbon fiber surface further demonstrates the high bond strength between the two.
[0052] like Figure 3 As shown, the bonding surface between the epoxy resin infiltrant 2 and the Al2O3 ceramic support body 1 was observed. It can be seen that the interface is tightly bonded and mutually infiltrated without obvious cracks. Without any pretreatment, the two can still achieve good bonding quality, which can ensure that the part has corresponding strength.
[0053] Comparative Example 1
[0054] The difference between this comparative example and Example 1 is that this comparative example only prints an Al2O3 entity with the same length, width, and height as the biomimetic layered spiral continuous carbon fiber reinforced ceramic matrix composite material in Example 1. The specific steps are:
[0055] (1) Draw a three-dimensional model of Al2O3 ceramic material. The model structure and parameters are as follows: length 35mm, width 9mm, height 9mm.
[0056] (2) Reduced photopolymerization 3D printing:
[0057] First, epoxy resin E51, 1,6-hexanediol diacrylate (HDDA), and trimethylolpropane triacrylate (TMPTA) were mixed in a ratio of 1:1:1. 1 wt.% of 2-hydroxy-2-methyl-1-phenyl-1-propanone was then added. Ultrasonic dispersion and stirring were performed using an ultrasonic disperser and an electric stirrer for 20 minutes to obtain a photosensitive resin premix. Next, 500 nm Al2O3 powder was sieved using a vibrating screen to remove agglomerated lumps to facilitate slurry preparation. 500 nm and 100 nm Al2O3 powders and 1 wt.% of magnesium oxide powder were thoroughly mixed. The mixed powders were then added to the photosensitive resin premix to a mass fraction of 75%. Finally, the premixed slurry was stirred at a speed of 1500 r / min using an electric stirrer for 1 hour. At the same time, the slurry was ultrasonically dispersed using an ultrasonic disperser. After stirring, the evenly mixed ceramic slurry was placed in a vacuum drying oven and defoamed at a negative pressure of -80 kPa for 10 minutes.
[0058] The model from step (1) was printed using v-photopolymerization 3D printing with the following printing parameters: slice thickness of 50 μm, laser power of 110 mW, and scanning interval of 30 μm. After printing, the alumina green body was cleaned with anhydrous ethanol to remove excess epoxy resin from its surface; then, the alumina green body was placed in a UV curing oven for 15 minutes and finally placed in a vacuum drying oven and dried at 70°C and atmospheric pressure for 3 hours.
[0059] (3) Degreasing and sintering:
[0060] The Al2O3 green body obtained by solidification in step (2) is placed in a crucible and then sent to a box furnace for degreasing. After degreasing, it is returned to the box furnace and sintered at 1600°C for 2 hours to obtain a dense Al2O3 material.
[0061] Comparative Example 2
[0062] The difference between this comparative example and Example 1 is that the central axis of the five-layer channel in this comparative example is rotated 22.5° from top to bottom layer by layer, and no 1K carbon fiber bundle is inserted into the channel during the infiltration process. The specific steps are as follows:
[0063] (1) Draw a three-dimensional model of a biomimetic layered spiral ceramic scaffold. The model structure and parameters are as follows:
[0064] The ceramic support body is 35mm long, 9mm wide, and 9mm high, with five layers of channels arranged inside. The channel interface is rectangular, 2mm long and 1.2mm high. The central axis of the five layers of channels rotates 22.5° from top to bottom. The top layer has three channels, and the central axis of the channels is parallel to the length of the ceramic support body. The top channel is 0.5mm away from the top of the ceramic support body, the distance between adjacent layers is 0.5mm, and the distance between adjacent channels in each layer is 0.8mm. The total volume of the channels is 40.04% of the volume of the ceramic support body.
[0065] (2) Reduced photopolymerization 3D printing:
[0066] First, epoxy resin E51, 1,6-hexanediol diacrylate (HDDA), and trimethylolpropane triacrylate (TMPTA) were mixed in a ratio of 1:1:1. 1 wt.% of 2-hydroxy-2-methyl-1-phenyl-1-propanone was then added. Ultrasonic dispersion and stirring were performed using an ultrasonic disperser and an electric stirrer for 20 minutes to obtain a photosensitive resin premix. Next, 500 nm Al2O3 powder was sieved using a vibrating screen to remove agglomerated lumps to facilitate slurry preparation. 500 nm and 100 nm Al2O3 powders and 1 wt.% of magnesium oxide powder were thoroughly mixed. The mixed powders were then added to the photosensitive resin premix to a mass fraction of 75%. Finally, the premixed slurry was stirred at a speed of 1500 r / min using an electric stirrer for 1 hour. At the same time, the slurry was ultrasonically dispersed using an ultrasonic disperser. After stirring, the evenly mixed ceramic slurry was placed in a vacuum drying oven and defoamed at a negative pressure of -80 kPa for 10 minutes.
[0067] The model of step (1) was printed using v-photopolymerization 3D printing with the following printing parameters: slice layer thickness of 50 μm, laser power of 110 mW, and scanning pitch of 30 μm. After printing, the support structure was separated from the alumina green body; then, the alumina green body was cleaned with anhydrous ethanol to remove excess epoxy resin on its surface; then, the uncured ceramic slurry in the gaps of the alumina green body was cleaned with an air compressor; then, the cleaned alumina green body was placed in an ultrasonic cleaner for ultrasonic cleaning; then, the alumina green body was placed in a UV curing box for curing for 15 minutes to cure the unformed part; finally, it was placed in a vacuum drying oven and dried at a constant temperature and pressure of 70°C for 3 hours.
[0068] (3) Degreasing and sintering:
[0069] The Al2O3 green body obtained by solidification in step (2) is placed in a crucible and then sent to a box furnace for degreasing. After degreasing, it is returned to the box furnace and sintered at 1600°C for 2 hours to obtain a dense Al2O3 support body.
[0070] (4) Infiltration:
[0071] Add epoxy resin impregnant to the Al2O3 support body obtained in step (3) until the epoxy resin impregnant completely immerses the Al2O3 support body and the carbon fiber bundle, and then cure in a vacuum oven at 95°C for 25 minutes. After taking it out, use alcohol wipes to clean the excess resin on the surface. After cleaning, place it in a vacuum drying oven again and keep it at a constant temperature of 125°C for 3 hours to completely cure it. The epoxy resin impregnant used is composed of epoxy resin (E51 / 618), curing agent methyltetrahydrophthalic anhydride (MTHPA) and curing accelerator (DMP-30). The molar ratio of the epoxy value of the epoxy resin to the molar amount of the anhydride of MTHPA is 4:3, and the added amount of DMP-30 is 0.1wt% of the epoxy resin impregnant.
[0072] Comparative Example 3
[0073] The difference between this comparative example and Example 1 is that the central axis of the five-layer channel in this comparative example is rotated 22.5° from top to bottom layer by layer. The specific preparation method is as follows:
[0074] (1) Draw a three-dimensional model of a biomimetic layered spiral ceramic scaffold. The model structure and parameters are as follows:
[0075] The ceramic support body is 35mm long, 9mm wide, and 9mm high, with five layers of channels arranged inside. The channel interface is rectangular, 2mm long and 1.2mm high. The central axis of the five layers of channels rotates 22.5° from top to bottom. The top layer has three channels, and the central axis of the channels is parallel to the length of the ceramic support body. The top channel is 0.5mm away from the top of the ceramic support body, the distance between adjacent layers is 0.5mm, and the distance between adjacent channels in each layer is 0.8mm. The total volume of the channels accounts for 40.04% of the volume of the ceramic support body.
[0076] (2) Reduced photopolymerization 3D printing:
[0077] First, epoxy resin E51, 1,6-hexanediol diacrylate (HDDA), and trimethylolpropane triacrylate (TMPTA) were mixed in a ratio of 1:1:1. 1 wt.% of 2-hydroxy-2-methyl-1-phenyl-1-propanone was then added. Ultrasonic dispersion and stirring were performed using an ultrasonic disperser and an electric stirrer for 20 minutes to obtain a photosensitive resin premix. Next, 500 nm Al2O3 powder was sieved using a vibrating screen to remove agglomerated lumps to facilitate slurry preparation. 500 nm and 100 nm Al2O3 powders and 1 wt.% of magnesium oxide powder were thoroughly mixed. The mixed powders were then added to the photosensitive resin premix to a mass fraction of 75%. Finally, the premixed slurry was stirred at a speed of 1500 r / min using an electric stirrer for 1 hour. At the same time, the slurry was ultrasonically dispersed using an ultrasonic disperser. After stirring, the evenly mixed ceramic slurry was placed in a vacuum drying oven and defoamed at a negative pressure of -80 kPa for 10 minutes.
[0078] The model of step (1) was printed using v-photopolymerization 3D printing with the following printing parameters: slice layer thickness of 50 μm, laser power of 110 mW, and scanning pitch of 30 μm. After printing, the support structure was separated from the alumina green body; then, the alumina green body was cleaned with anhydrous ethanol to remove excess epoxy resin on its surface; then, the uncured ceramic slurry in the gaps of the alumina green body was cleaned with an air compressor; then, the cleaned alumina green body was placed in an ultrasonic cleaner for ultrasonic cleaning; then, the alumina green body was placed in a UV curing box for curing for 15 minutes to cure the unformed part; finally, it was placed in a vacuum drying oven and dried at a constant temperature and pressure of 70°C for 3 hours.
[0079] (3) Degreasing and sintering:
[0080] The Al2O3 green body obtained by solidification in step (2) is placed in a crucible and then sent to a box furnace for degreasing. After degreasing, it is returned to the box furnace and sintered at 1600°C for 2 hours to obtain a dense Al2O3 support body.
[0081] (4) Penetration into carbon fiber bundles and impregnation:
[0082] Insert the 1K carbon fiber bundle into all the pores of the Al2O3 support body obtained in step (3), then add the epoxy resin impregnant until the epoxy resin impregnant completely immerses the Al2O3 support body and the carbon fiber bundle, and then cure it in a vacuum oven at 95°C for 25 minutes. After taking it out, use alcohol wipes to clean the excess resin on the surface. After cleaning, place it in a vacuum drying oven again and keep it at a constant temperature of 125°C for 3 hours to fully cure it. The epoxy resin impregnant used is composed of epoxy resin (E51 / 618), curing agent methyltetrahydrophthalic anhydride (MTHPA) and curing accelerator (DMP-30). The molar ratio of the epoxy value of the epoxy resin to the molar amount of the anhydride of MTHPA is 4:3, and the amount of DMP-30 added is 0.1wt% of the epoxy resin impregnant.
[0083] Comparative Example 4
[0084] The difference between this comparative example and Example 1 is that the 1K carbon fiber bundle is not inserted into the pores during the infiltration process. The specific preparation method is as follows:
[0085] (1) Draw a three-dimensional model of a biomimetic layered spiral ceramic scaffold. The model structure and parameters are as follows:
[0086] The ceramic support body is 35mm long, 9mm wide, and 9mm high, with five layers of channels inside. The channel interface is rectangular, 2mm long, and 1.2mm high. The central axis of the five layers of channels rotates 45° from top to bottom. The top layer has three channels, and the central axis of the channels is parallel to the length of the ceramic support body. The top channel is 0.5mm away from the top of the ceramic support body, the distance between adjacent layers is 0.5mm, and the distance between adjacent channels in each layer is 0.8mm. The total volume of the channels accounts for approximately 40.04% of the volume of the ceramic support body.
[0087] (2) Reduced photopolymerization 3D printing:
[0088] First, epoxy resin E51, 1,6-hexanediol diacrylate (HDDA), and trimethylolpropane triacrylate (TMPTA) were mixed in a ratio of 1:1:1. 1 wt.% of 2-hydroxy-2-methyl-1-phenyl-1-propanone was then added. Ultrasonic dispersion and stirring were performed using an ultrasonic disperser and an electric stirrer for 20 minutes to obtain a photosensitive resin premix. Next, 500 nm Al2O3 powder was sieved using a vibrating screen to remove agglomerated lumps to facilitate slurry preparation. 500 nm and 100 nm Al2O3 powders and 1 wt.% of magnesium oxide powder were thoroughly mixed. The mixed powders were then added to the photosensitive resin premix to a mass fraction of 75%. Finally, the premixed slurry was stirred at a speed of 1500 r / min using an electric stirrer for 1 hour. At the same time, the slurry was ultrasonically dispersed using an ultrasonic disperser. After stirring, the evenly mixed ceramic slurry was placed in a vacuum drying oven and defoamed at a negative pressure of -80 kPa for 10 minutes.
[0089] The model of step (1) was printed using v-photopolymerization 3D printing with the following printing parameters: slice layer thickness of 50 μm, laser power of 110 mW, and scanning pitch of 30 μm. After printing, the support structure was separated from the alumina green body; then, the alumina green body was cleaned with anhydrous ethanol to remove excess epoxy resin on its surface; then, the uncured ceramic slurry in the gaps of the alumina green body was cleaned with an air compressor; then, the cleaned alumina green body was placed in an ultrasonic cleaner for ultrasonic cleaning; then, the alumina green body was placed in a UV curing box for curing for 15 minutes to cure the unformed part; finally, it was placed in a vacuum drying oven and dried at a constant temperature and pressure of 70°C for 3 hours.
[0090] (3) Degreasing and sintering:
[0091] The Al2O3 green body obtained by solidification in step (2) is placed in a crucible and then sent to a box furnace for degreasing. After degreasing, it is returned to the box furnace and sintered at 1600°C for 2 hours to obtain a dense Al2O3 support body.
[0092] (4) Infiltration:
[0093] Add epoxy resin impregnant to the Al2O3 support body obtained in step (3) until the epoxy resin impregnant completely immerses the Al2O3 support body and the carbon fiber bundle, and then cure in a vacuum oven at 95°C for 25 minutes. After taking it out, use alcohol wipes to clean the excess resin on the surface. After cleaning, place it in a vacuum drying oven again and keep it at a constant temperature of 125°C for 3 hours to completely cure it. The epoxy resin impregnant used is composed of epoxy resin (E51 / 618), curing agent methyltetrahydrophthalic anhydride (MTHPA) and curing accelerator (DMP-30). The molar ratio of the epoxy value of the epoxy resin to the molar amount of the anhydride of MTHPA is 4:3, and the added amount of DMP-30 is 0.1wt% of the epoxy resin impregnant.
[0094] Comparative Example 5
[0095] The difference between this comparative example and Example 1 is that the carbon fiber layers in this comparative example are not rotated, the central axis of the five layers of channels are parallel to the length direction of the ceramic support body, and each layer contains three channels. The specific preparation method is as follows:
[0096] (1) Draw a three-dimensional model of a biomimetic layered spiral ceramic scaffold. The model structure and parameters are as follows:
[0097] The ceramic support body is 35mm long, 9mm wide, and 9mm high. It contains five layers of channels, each with a rectangular interface measuring 2mm long and 1.2mm high. The central axis of the five channels runs parallel to the length of the ceramic support body. Each layer has three channels, with the top channel 0.5mm from the top of the support body. The distance between adjacent channels is 0.5mm, and the distance between adjacent channels within each layer is 0.8mm. The total volume of the channels accounts for 44.4% of the total volume of the ceramic support body.
[0098] (2) Reduced photopolymerization 3D printing:
[0099] First, epoxy resin E51, 1,6-hexanediol diacrylate (HDDA), and trimethylolpropane triacrylate (TMPTA) were mixed in a ratio of 1:1:1. 1 wt.% of 2-hydroxy-2-methyl-1-phenyl-1-propanone was then added. Ultrasonic dispersion and stirring were performed using an ultrasonic disperser and an electric stirrer for 20 minutes to obtain a photosensitive resin premix. Next, 500 nm Al2O3 powder was sieved using a vibrating screen to remove agglomerated lumps to facilitate slurry preparation. 500 nm and 100 nm Al2O3 powders and 1 wt.% of magnesium oxide powder were thoroughly mixed. The mixed powders were then added to the photosensitive resin premix to a mass fraction of 75%. Finally, the premixed slurry was stirred at a speed of 1500 r / min using an electric stirrer for 1 hour. At the same time, the slurry was ultrasonically dispersed using an ultrasonic disperser. After stirring, the evenly mixed ceramic slurry was placed in a vacuum drying oven and defoamed at a negative pressure of -80 kPa for 10 minutes.
[0100] The model of step (1) was printed using v-photopolymerization 3D printing with the following printing parameters: slice layer thickness of 50 μm, laser power of 110 mW, and scanning pitch of 30 μm. After printing, the support structure was separated from the alumina green body; then, the alumina green body was cleaned with anhydrous ethanol to remove excess epoxy resin on its surface; then, the uncured ceramic slurry in the gaps of the alumina green body was cleaned with an air compressor; then, the cleaned alumina green body was placed in an ultrasonic cleaner for ultrasonic cleaning; then, the alumina green body was placed in a UV curing box for curing for 15 minutes to cure the unformed part; finally, it was placed in a vacuum drying oven and dried at a constant temperature and pressure of 70°C for 3 hours.
[0101] (3) Degreasing and sintering:
[0102] The Al2O3 green body obtained by solidification in step (2) is placed in a crucible and then sent to a box furnace for degreasing. After degreasing, it is returned to the box furnace and sintered at 1600°C for 2 hours to obtain a dense Al2O3 support body.
[0103] (4) Penetration into carbon fiber bundles and impregnation:
[0104] Insert the 1K carbon fiber bundle into all the pores of the Al2O3 support body obtained in step (3), then add the epoxy resin impregnant until the epoxy resin impregnant completely immerses the Al2O3 support body and the carbon fiber bundle, and then cure it in a vacuum oven at 95°C for 25 minutes. After taking it out, use alcohol wipes to clean the excess resin on the surface. After cleaning, place it in a vacuum drying oven again and keep it at a constant temperature of 125°C for 3 hours to fully cure it. The epoxy resin impregnant used is composed of epoxy resin (E51 / 618), curing agent methyltetrahydrophthalic anhydride (MTHPA) and curing accelerator (DMP-30). The molar ratio of the epoxy value of the epoxy resin to the molar amount of the anhydride of MTHPA is 4:3, and the amount of DMP-30 added is 0.1wt% of the epoxy resin impregnant.
[0105] Test example
[0106] The materials of Example 1 and Comparative Examples 1 to 5 were subjected to performance tests. The flexural strength was measured using a three-point bending test in accordance with ASTM C1161-13, and the fracture toughness was measured using a single-edge notched beam bending test in accordance with ASTM C1421-99. The test results are shown in Table 1.
[0107] Table 1 Bending strength and fracture toughness of materials of Example 1 and Comparative Examples 1 to 5
[0108]
[0109]
[0110] As can be seen from Table 1, the biomimetic layered spiral continuous carbon fiber reinforced ceramic matrix composite of Example 1 has the highest flexural strength and fracture toughness. Compared with Comparative Example 1, the flexural strength increased by 192.9% and the fracture toughness increased by 191.44%. Compared with Comparative Example 2, the flexural strength increased by 52.69% and the fracture toughness increased by 142.56%. Compared with Comparative Example 3, the flexural strength increased by 21.81% and the fracture toughness increased by 10.82%. Compared with Comparative Example 4, the flexural strength increased by 2.98% and the fracture toughness increased by 78%. Although Comparative Example 5 has the highest flexural strength, its fracture toughness increased by only 82.1% compared with Comparative Example 1, which is far lower than the improvement of the composite material of Example 1. This shows that Example 1 can achieve a significant improvement in both material strength and toughness.
[0111] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. A bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material, characterized in that: It comprises a ceramic support body, wherein a plurality of layers of channels are arranged inside the ceramic support body, and each layer of channels is provided with a plurality of channels parallel to each other; the central axis of the plurality of layers of channels is rotated layer by layer at a set angle along the layer extension direction, and the interior of the channels is filled with continuous carbon fiber reinforced thermosetting resin.
2. The bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The central axis of the topmost layer of the ceramic support body is parallel to the length direction of the ceramic support body.
3. The bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material according to claim 2, characterized in that: The planes where the channels of each layer are located are parallel to each other, the central axis of the multi-layer channels is rotated 45 degrees layer by layer along the direction of the vertical line of the plane where the channels of each layer are located, and 5 layers of channels are arranged inside the ceramic support body.
4. The bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: Each layer of channels is provided with at least three channels parallel to each other; the distances between adjacent channels in each layer of channels are kept the same; and the total volume of the channels accounts for more than 40% of the volume of the ceramic support body.
5. The bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The material of the ceramic support body is selected from one or more of aluminum oxide, silicon oxide or zirconium oxide.
6. The bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The continuous carbon fiber reinforced thermosetting resin comprises carbon fiber bundles and thermosetting resin arranged in sequence from inside to outside.
7. The bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material according to claim 6, characterized in that: The carbon fiber bundle is 1-2K carbon fiber; the thermosetting resin is selected from one or more of epoxy resin, bismaleimide resin, thermosetting polyimide resin, phenolic resin, cyanate resin or unsaturated polyester resin.
8. The bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material according to claim 6, characterized in that: The volume fraction of the carbon fiber in the continuous carbon fiber reinforced thermosetting resin is 3-8%.
9. The method for preparing the bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material according to any one of claims 1 to 8, characterized in that: The steps include: A ceramic support body green body is prepared by 3D printing, and the ceramic support body is obtained by degreasing and sintering. Continuous carbon fibers are inserted into the multilayer channels of the ceramic support body, and a thermosetting resin impregnant is used for infiltration. After curing, a bionic layered spiral continuous carbon fiber reinforced ceramic matrix composite material is obtained.
10. The preparation method according to claim 9, characterized in that: The 3D printing is v-photopolymerization 3D printing.
Citation Information
Patent Citations
Internal and external reinforced and toughened ceramic and preparation method thereof
CN115432999A
High-strength and high-toughness bionic ceramic / continuous fiber composite material and preparation method thereof
CN115991596A
Design method of porous spiral layered bionic structure
CN117828880A
Light tough fiber composite material imitating cavity ratchet scales and preparation method of light tough fiber composite material
CN118288629A
Method of manufacturing fibre reinforced composite structures
WO2022058702A1